Comparative Analysis of Fluorinated Anions for Polypyrrole Linear Actuator Electrolytes - Khuyen, Nguyen Quang (Polymers (Basel), 2019)
Either as salts or room temperature ionic liquids, fluorinated anion-based electrolytes have been a common choice for ionic electroactive polymer actuators, both linear and bending. In the present work, propylene carbonate solutions of four electrolytes of the three hugely popular anions—triflouromethanesulfonate, bis(trifluoromethane)sulfonimide, and hexafluorophosphate were compared and evaluated in polypyrrole linear actuators. The actuation direction, the characteristics—performance relations influence the behavior of the actuators. Isotonic Electro-chemo-mechanical deformation (ECMD) measurements were performed to study the response of the PPy/DBS samples. The highest strain for pristine PPy/DBS linear actuators was found in range of 21% for LiTFSI, while TBAPF(6) had the least cation involvement, suggesting the potential for application in durable and controllable actuators. Interesting cation effects on the actuation of the same anions (CF(3)SO(3)(−)) were also observed.